Examining The Problems Of Teachers In The Project Preparing And Implementation Processes According To Project Cycle Management Stages - Arabaci, İmam Bakır; Akilli, Ceyda (T.C. Milli Egitim Bakanligi, 2020)
The aim of the research is to classify the problems of school managers and teachers working in the educational organizations in Elazığ during the project preparation and implementation processes according to the project cycle management stages and to find solutions for these problems. The study was carried out according to the situation analysis technique that is one of the qualitative research methods. As data collection tool, semi-structured interview form created by the researcher was used. The sample group of the study was consisted of 50 school managers and teachers who worked in different grades of educational organizations in Elazığ. During the data analysis process, the answers of the sample group for the questions in the interview form were subjected to content analysis; frequencies and percentages were calculated. The results of the study indicate that: (1) The processes of project preparation and implementation gain experience, support cooperation among colleagues and students. (2) The most frequently encountered problems during the stage of preparing project ideas are defining original subjects and doubting on whether the subjects are functional or not. (3) In the project implementation stage, there may be some problems deriving from not having adequate information about project techniques. (4) A great number of the participants declared that educators need to get detailed training on projects in order to solve the problems encountered during project preparation and evaluation processes. © 2020, Milli Egitim. All Rights Reserved
Eğİtİmcİlerİn Proje Hazirlama Ve Yürütme Süreçlerİnde Karşilaştiklari Sorunlarin Proje Döngüsü Yönetİmİ Aşamalarina Göre İncelenmesİ
Keywords: Educational Projects; Project Cycle Management; School Development